2021
DOI: 10.3389/fpsyt.2021.602244
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mental Health Problems and Its Associated Factors Among Recovered COVID-19 Patients During the Pandemic: A Single-Center Study

Abstract: Introduction: The coronavirus disease 2019 (COVID-19), is profoundly affecting the mental health status. Although the burden of mental health problems has been reported in the general population and health care workers, little is known about the prevalence of mental health disorders among recovered COVID-19 patients and their associated factors.Methods: A cross-sectional telephonic-study of recovered COVID-19 patients with and without a history of hospitalization was conducted from April 20 to June 20, 2020, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 47 publications
(60 reference statements)
7
20
3
1
Order By: Relevance
“…During the primary screening, a total of 1597 records were obtained, in which 50 articles relevant to our review were extracted for full-text search. During the secondary screening, we went through the full-text of these articles and found 13 articles with 1,093 participants satisfying our inclusion criteria and included as a part of the analysis ( Figure 1 ) ( Janiri et al, 2021 , Morin et al, 2021 , Naidu et al, 2021 , Rass et al, 2021 , Khademi et al, 2021 , Liu et al, 2020 , de Graaf et al, 2021 , Mazza et al, 2020 , Martillo et al, 2021 , Parker et al, 2021 , Beck et al, 2021 , Tarsitani et al, 2021 , Poyraz et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…During the primary screening, a total of 1597 records were obtained, in which 50 articles relevant to our review were extracted for full-text search. During the secondary screening, we went through the full-text of these articles and found 13 articles with 1,093 participants satisfying our inclusion criteria and included as a part of the analysis ( Figure 1 ) ( Janiri et al, 2021 , Morin et al, 2021 , Naidu et al, 2021 , Rass et al, 2021 , Khademi et al, 2021 , Liu et al, 2020 , de Graaf et al, 2021 , Mazza et al, 2020 , Martillo et al, 2021 , Parker et al, 2021 , Beck et al, 2021 , Tarsitani et al, 2021 , Poyraz et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis reveals that pediatric patients, despite apparent clinical recovery at discharge, had obvious behavioral problems when evaluated approximately two months later. Extensive research has examined the mental health burden in adults discharged from hospital with COVID-19 in China ( Chen et al, 2020 ; Chen, Huang, et al, 2021 ; Chen, Ju, et al, 2021 ; Huang, Huang, et al, 2021 ; Huang, Xu, et al, 2021 ; Huang, Zhuang, et al, 2021 ; Ju et al, 2021 ; Liang et al, 2020 ; Liu, Bao, et al, 2020 ; Liu, Baumeister, et al, 2020 ; Putri et al, 2021 ; Qu et al, 2021 ; Tu et al, 2021 ; Wu, Chen, et al, 2020 ; Wu, Hu, et al, 2020 ; Xiong, Xu, et al, 2021 ; Xiong, Zhong, et al, 2021 ; Yuan et al, 2020 ), Italy ( Mattioli et al, 2021 ; Tomasoni et al, 2021 ), Australia ( Darley et al, 2021 ; Rass et al, 2021 ), Netherlands ( de Graaf et al, 2021 ; Vlake et al, 2021 ), the UK ( Halpin et al, 2021 ; Zavala et al, 2021 ), France ( Garrigues et al, 2020 ; Horn et al, 2021 ; Morin et al, 2021 ), Germany ( Augustin et al, 2021 ; Daher et al, 2020 ), Iran ( Khademi et al, 2021 ; Mirfazeli et al, 2022 ), Egypt ( Kamal et al, 2021 ), Brazil ( Damiano et al, 2022 ; Todt et al, 2021 ), the USA ( Daugherty et al, 2021 ; Graham et al, 2021 ; Jovanoski et al, 2021 ; Martillo et al, 2021 ), and Korea ( Chang & Park, 2020 ) (see details in e Table B), reporting substantial psychological distress in the first few months after infection. However, there is limited information available on pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers on the frontlines have similarly reported heightened levels of stress, anxiety, and depression during the COVID-19 pandemic due to factors such as immediate exposure to the virus and death, concerns over infection of self and family members, lack of personal protective equipment, overwork, and burnout (Kock et al, 2021 ; Moitra et al, 2021 ; Mosheva et al, 2021 ). Emerging research has also identified that individuals who have recovered or are in-recovery after COVID-19 infection may experience depression or PTSS (Khademi et al, 2021 ; Vindegaard & Benros, 2020 ).…”
Section: Introductionmentioning
confidence: 99%